Globalization in the food sector and poverty - Leo Dörr; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2024)
This paper provides new evidence on the globalizationâ exteuro'poverty nexus. We innovate by using an indicator of globalization in the food sector, finding evidence of a significantly aggravating impact on poverty prev-alence, adding to earlier studies that use indicators of general globalization. The opening of food markets since the mid-1990s in Latin America might have accounted for approximately 2 additional percentage points of the population living below the absolute poverty line of 2 a day in our sample.
Keywords: F66; Q17; Q18; 330; Economic Impacts of Globalization; Agriculture in International Trade; Food Policy